From growing crops to growing cities: SRP's transition from ag to urban - Dudley, Shelly C., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2008)
This presentation will visually show, through the use of historic and contemporary photographs, that reclamation was a cornerstone of growth in the West: providing a stable water supply for crops, transforming the desert to the farmlands, and now farmlands to the development of cities businesses and communities; developing power, to operate the irrigation pumps, light the homes, and now power our industries. SRP, as one of the first multi-purpose reclamation projects authorized by the federal government, provided irrigation water to the settlers of the Salt River Valley at the beginning of the twentieth century. Now, over one hundred years later, SRP continues that tradition and is still delivering water to its shareholders and customers, but now in an urban setting.
Urbanization of irrigated land and water transfers
SRP's transition from ag to urban
Not digitized by CSUL Digital Services.
Presented at Urbanization of irrigated land and water transfers: a USCID water management conference on May 28-31, 2008 in Scottsdale, Arizona.